Physical infrastructure and international competitiveness at the firm level implications for developing economics - Mahmood, Amir (1999)
Among other factors, international competitiveness at the firm level depends on the provisions of well-maintained and efficient physical infrastructure networks. Infrastructure networks, such as telecommunications, electricity, gas, irrigation, and transport services, play a strong complementary role in firms? ability to create and maintain their competitiveness through creating more value than their competitors. In developing countries, the issues relating to inefficiencies in the provision of infrastructure services are closely linked with firms? ability to acquire international competitiveness. In many instances, efficiency, as well as adequacy norms of infrastructure networks, can be achieved by changing the institutional setting and creating a competitive environment in the provision of infrastructure services.
Includes bibliographical references (pages 12-13).